Locus of Control and the Labor Market - Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2014)
This paper reviews the role of locus of control in the labor market. I begin with a discussion of the conceptual origins of locus of control, including its relationship to related concepts such as self-efficacy, motivation, and self-control. The relationship between locus of control and labor market success is then summarized. In doing so, I pay careful attention to what we know about three potential mechanisms human capital investments, hiring decisions, and optimal incentive contracts through which locus of control might operate. Finally, the broader implications of these relationships for public policy and future research are discussed.
Keywords: J01; J08; 330; locus of control; labor market; behavioral economics